(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Hyperthyroidism (Graves’ disease, diffuse toxic goiter) is a pathological condition of the body, which is caused by an increased content of T3 and T4 hormones in the blood and characteristic changes in various body systems, in particular the cardiovascular and nervous systems, with the development of endocrine ophthalmoplegia.